The Relationship Between Organization Learning Culture, Leader-Member Exchange with Job Satisfaction and the Mediating Role of Human Resource Management Practices Among the Public Sector in the Sultanate of Oman - Murshid Sulaiman Nasser Alkharousi (Universiti Sains Islam Malaysia, 2024)
Matric: 4140161 (FKP)